2006
DOI: 10.1179/146532806x90619
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal group B streptococcal infection at the University Hospital of the West Indies, Jamaica: a 10-year experience

Abstract: Although the incidence of GBS infection is relatively low at UHWI, further reduction in the incidence might be achieved by implementation of measures to prevent perinatal transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The Americas Martin et al 41 Vaciloto et al 42 Bell et al 43 Trotman et al 44 Castrodale et al 45 Chen et al 46 Hyde et al 47 Mayor-Lynn et al 48 Phares et al 49 Puopolo et al 50 CDC et al 51 Stoll et al 52 CDC et al 53 Brooks et al 54 Cordero et al 55 Jordan et al 56 Subtotal (I 2 =97·4%, p=0·000)…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Americas Martin et al 41 Vaciloto et al 42 Bell et al 43 Trotman et al 44 Castrodale et al 45 Chen et al 46 Hyde et al 47 Mayor-Lynn et al 48 Phares et al 49 Puopolo et al 50 CDC et al 51 Stoll et al 52 CDC et al 53 Brooks et al 54 Cordero et al 55 Jordan et al 56 Subtotal (I 2 =97·4%, p=0·000)…”
Section: Data Extractionmentioning
confidence: 99%
“…The Americas Trotman et al 44 Castrodale et al 45 Hyde et al 47 Mayor-Lynn et al 48 Phares et al 49 Puopolo et al 50 Brooks et al 54 Cordero et al 55 Jordan et al 56 Subtotal (I 2 =86·7%, p=0·000) Africa Gray et al 58 Milledge et al 73 Sigauque et al 74 Subtotal (I 2 =59·9%, p=0·083) Western Pacific Matsubara et al 75 Park et al 96 Cho et al 77 Chang et al 78 …”
Section: Year Europementioning
confidence: 99%
“…Disease onset and clinical presentation. Most cases occur within the first 24 to 48 hours 23 , 25 , 29 31 , and more than half of early-onset disease occurs in term (≥37 weeks gestation) infants: studies from sub-Saharan Africa have reported the proportion of pre-term infants among infants with early-onset disease to range from 10 to 46% 22 , 24 , 25 . Respiratory distress has been described as one of the most common presenting symptoms, ranging from 68% (South Africa, single hospital retrospective review, 1997–1999) 25 to 83% (South Africa, surveillance at three secondary-tertiary care hospitals, 2012–2014) 24 .…”
Section: Diseases and Sequelae Caused By Gbs And Population At Riskmentioning
confidence: 99%
“…0.72 cases per 1000 live births in the UK (Heath et al, 2004). The anomalously low incidence of S. agalactiae neonatal disease in the developing world may reflect problems in accurate data collection (Johri et al, 2006) and high disease burdens have been reported recently in studies carried out in Jamaica and Malawi (Trotman & Bell, 2006;Gray et al, 2007). S. agalactiae is also emerging as a cause of disease in the elderly (Edwards & Baker, 2005).…”
Section: Introductionmentioning
confidence: 99%